2020
DOI: 10.1021/acssensors.0c01037
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamond Relaxometry-Based Detection of Free-Radical Species When Produced in Chemical Reactions in Biologically Relevant Conditions

Abstract: Diamond magnetometry is a quantum sensing method involving detection of magnetic resonances with nanoscale resolution. For instance, T1 relaxation measurements, inspired by equivalent concepts in magnetic resonance imaging (MRI), provide a signal that is equivalent to T1 in conventional MRI but in a nanoscale environment. We use nanodiamonds (between 40 and 120 nm) containing ensembles of specific defects called nitrogen vacancy (NV) centers. To perform a T1 relaxation measurement, we pump the NV center in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
111
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(112 citation statements)
references
References 43 publications
1
111
0
Order By: Relevance
“…This time, called relaxation time or T1 , is shortened by the presence of spin noise ( 46 ) from free radicals. In a previous work ( 45 ), we found that, under controlled conditions, the obtained plots could be fitted with the following equation …”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…This time, called relaxation time or T1 , is shortened by the presence of spin noise ( 46 ) from free radicals. In a previous work ( 45 ), we found that, under controlled conditions, the obtained plots could be fitted with the following equation …”
Section: Resultsmentioning
confidence: 89%
“…Gray lines show individual experiments on single cells. The left gray axis represents the approximated concentration determined from a calibration with *OH radicals in solution from the previous work ( 45 ). The experiments were repeated nine times.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations